Constitutional Hazard: The California Resale Royalty Act and the Futility of State-Level Implementation of Droit de Suite Legislation - Kumar, Nithin (The Columbia Journal of Law & the Arts, 2014)
Répétition d’un Ballet, the famous painting by French artist Edgar Degas, sold for 401,000 in 1965. The jubilant seller bragged that Degas originally asked a mere 100 for the painting. In his early career, celebrated American artist Norman Rockwell sold original works like Homecoming Marine and Breaking Home Ties for a few hundred dollars each. In the last decade, these paintings were resold for 9.2 million and 15.4 million at Sotheby’s auctions, but the Rockwell estate received nothing in these transactions. Over the centuries, great wealth in the arts has rarely translated into great wealth for the artist. Since its inception in France, the resale royalty known as the droit de suite has aimed at remedying this perceived injustice. Although a resale royalty right is currently recognized in seventy-nine jurisdictions, California is the only American jurisdiction to have adopted it. The California Resale Royalties Act (CRRA), enacted in 1976, grants visual artists the right to collect a 5% royalty on the total sales price each time their works are resold in California or by a resident of California. The fate of the California Resale Royalty Act, however, currently rests with the U.S. Court of Appeals for the Ninth Circuit.